The Relationship between Levels of Knowledge and Anxiety on Blood Sugar Levels in Diabetes Mellitus Patients at RSAU dr. Siswanto - Yohanes Wahyu Nugroho; Dewi Anggraeni (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Diabetes is a disease characterized by high blood sugar levels in the urine due to disruption of metabolism due to the production and function of the hormone insulin not running as it should. Diabetes can cause psychological problems including anxiety levels and even stress. Patients with diabetes mellitus who have high knowledge can maintain a healthy diet and lifestyle behavior so that blood sugar levels can always be controlled. Objective: This study aims to analyze the relationship between knowledge level and anxiety to blood sugar levels in patients with Diabetes Mellitus at RSAU dr. Siswanto. Method: This study is a quantitative research with a correlational approach. The population in this study is 64 people with diabetes mellitus at RSAU dr. Siswanto Karanganyar for the period of March 2024. The sampling technique uses total sampling, so that the number of samples in this study is 64 patients. The instrument used in this study is in the form of a questionnaire. To analyze bivariate data using the Kendal's tau test. Result: The results of the research analysis on the relationship between knowledge level and blood sugar levels obtained a significance value of 0.001 less than 0.05. The results of the research analysis on the relationship between anxiety and blood sugar levels obtained a significance value of 0.031 less than 0.05. The results of the multivariate test showed a significance value of 0.000 < 0.05 and an Fcal value of 30.475. Conclusion: there is a significant relationship between the level of knowledge and blood sugar levels of patients with diabetes mellitus in RSAU dr. Siswanto Karanganyar. There was a significant relationship between anxiety and blood sugar levels in patients with diabetes mellitus in RSAU dr. Siswanto Karanganyar. There was a significant relationship between knowledge and anxiety on blood sugar levels of patients with diabetes mellitus in RSAU dr. Siswanto Karanganyar.